Evaluasi Kritis Pemilihan Metodologi Pengembangan Sistem dalam Transformasi Digital Lembaga Pendidikan Islam - Debi Tiara Wulan Dari; Saipul Annur; Ade Rosad (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The acceleration of digital transformation within Islamic educational institutions has significantly increased the need for effective and context-sensitive system development methodologies. The success of digital learning systems is not solely determined by technological infrastructure, but also by the strategic selection of development approaches. This study aims to critically analyze the characteristics of the Waterfall and Agile methodologies and to assess their relevance within Islamic educational institutions. Employing a qualitative design through library research, this study reviews scholarly books and peer-reviewed journal articles published from 2020 onward. The findings indicate that the Waterfall model offers structural clarity, detailed documentation, and strong managerial oversight, making it suitable for relatively stable administrative systems. In contrast, the Agile model promotes flexibility, iterative improvement, and active stakeholder participation, which are essential in dynamic academic environments. Given the formal yet evolving nature of Islamic educational institutions, a hybrid model integrating systematic planning with adaptive development is considered the most appropriate strategy. The study concludes that methodological alignment with institutional culture and human resource readiness is a critical factor in achieving sustainable digital transformation.